2021
DOI: 10.1038/s41419-021-03601-2
|View full text |Cite
|
Sign up to set email alerts
|

Circ-HMGA2 (hsa_circ_0027446) promotes the metastasis and epithelial-mesenchymal transition of lung adenocarcinoma cells through the miR-1236-3p/ZEB1 axis

Abstract: Lung adenocarcinoma (LUAD) has high incidence and mortality rates worldwide; however, its detailed molecular pathology remains unclear. Although circRNAs have gradually been identified as molecules that are differentially expressed in tumors and play key roles in tumor progression, their role in LUAD is poorly understood. Through microarray analysis, we obtained the circRNA expression profile of LUAD and found that circ-HMGA2 (hsa_circ_0027446), a novel RNA, is highly expressed in LUAD. The high expression of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 38 publications
1
29
0
Order By: Relevance
“…Among the abnormally expressed circRNAs, upregulated circRNAs were more common than downregulated circRNAs in these published data set. Also, previous studies have focused on that some circRNAs are upregulated in LUAD and display oncogenic functions in LUAD (18)(19)(20)(21). Heatmap analysis showed that hsa_circ_0046263 (circP4HB), hsa_circ_0006006, hsa_circ_0057105, hsa_ circ_0057104, hsa_circ_0000520, and hsa_circ_0003528 were all simultaneously and aberrantly expressed in LUAD tissues compared to para-tumor tissues (Figure 1A,1B).…”
Section: Circp4hb Triggers Gsh Synthesismentioning
confidence: 92%
“…Among the abnormally expressed circRNAs, upregulated circRNAs were more common than downregulated circRNAs in these published data set. Also, previous studies have focused on that some circRNAs are upregulated in LUAD and display oncogenic functions in LUAD (18)(19)(20)(21). Heatmap analysis showed that hsa_circ_0046263 (circP4HB), hsa_circ_0006006, hsa_circ_0057105, hsa_ circ_0057104, hsa_circ_0000520, and hsa_circ_0003528 were all simultaneously and aberrantly expressed in LUAD tissues compared to para-tumor tissues (Figure 1A,1B).…”
Section: Circp4hb Triggers Gsh Synthesismentioning
confidence: 92%
“… 10 In the last few years, many circRNAs have been authenticated and found to be involved in multiple biological processes including the cell cycle, proliferation, invasion, migration, apoptosis, angiopoiesis, epithelial-mesenchymal transition, and immune escape. 11 , 12 , 13 , 14 circRNAs act as “miRNA sponges” and bind microRNAs (miRNAs) to abolish the regulation of target genes induced by miRNAs. 15 , 16 hsa_circ_0000936, a subtype of circSHKBP1, is an oncogenic circRNA derived from the SHKBP1 gene and is reported to promote gastric cancer progression by regulating the miR-582–3p/HUR/vascular endothelial growth factor (VEGF) axis and suppressing heat shock protein 90 (HSP90) degradation.…”
Section: Introductionmentioning
confidence: 99%
“…As a number of studies have indicated, circRNAs can function as competing endogenous RNAs (ceRNAs) that sponge miRNAs or bind to proteins to regulate the biological behavior of cells ( Thomson and Dinger, 2016 ). There is convincing evidence verifying that circRNA plays an essential role in tumor progression—for example, circHMGA2 can regulate the development of lung cancer cells through the miR-1236-3p/ZEB1 axis ( Yu et al, 2021a ). Hsa_circ_0001666 can boost the development of thyroid carcinoma upregulation of ETV4 ( Qi et al, 2021 ), and circHIPK3 can influence myoblast progression by regulating the miR-7/TCF12 axis ( Gao et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%